THE SOCIO-PEDAGOGICAL NECESSITY OF PREPARING FUTURE BIOLOGY TEACHERS FOR THE FORMATION OF BIOETHICAL KNOWLEDGE IN STUDENTS (Scientific journal of the Fergana State University, 2024)
In this article, the theoretical-methodological foundations of preparing future biology teachers for the formation of bioethical knowledge in students, and the practical methodical system of preparing for the formation of bioethical knowledge are thoroughly researched. The socio-pedagogical necessity of preparing future biology teachers for the formation of bioethical knowledge in students is analyzed.